2000
DOI: 10.1177/00912700022009558
|View full text |Cite
|
Sign up to set email alerts
|

Who Needs Individual Bioequivalence Studies for Narrow Therapeutic Index Drugs? A Case for Warfarin

Abstract: Warfarin is, among drugs, considered to have a narrow therapeutic index for which individual bioequivalence has been suggested. To establish the propriety of "switching," an individual bioequivalence study involving a replicate-design study and three "switchings" in healthy subjects was undertaken using the U.S.-brand warfarin sodium tablet and a generic product. A randomized, single-center, open-label, single-dose, four-way crossover replicate bioequivalence study was performed in 24 healthy male volunteers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…The sample size for the proof‐of‐concept study ( n = 12 evaluable subjects) was calculated based on 80% power to detect a 25% change in the primary endpoints with a type I error of 0.05; the primary endpoints were the treatment/control ratios of log‐transformed AUC 0–48 (( S )‐warfarin) or AUC 0–inf (midazolam) and C max (( S )‐warfarin and midazolam), and the predefined no effect range was 0.75–1.33 5 , 6 . Intraindividual variability in midazolam and warfarin AUC and C max were assumed to be ~20% 46 48 . Secondary outcomes, t 1/2 and t max , were evaluated using a paired two‐tailed Student's t ‐test on log‐transformed data or Wilcoxon signed‐rank test as appropriate, with 90% confidence intervals and ranges reported for t 1/2 and t max , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size for the proof‐of‐concept study ( n = 12 evaluable subjects) was calculated based on 80% power to detect a 25% change in the primary endpoints with a type I error of 0.05; the primary endpoints were the treatment/control ratios of log‐transformed AUC 0–48 (( S )‐warfarin) or AUC 0–inf (midazolam) and C max (( S )‐warfarin and midazolam), and the predefined no effect range was 0.75–1.33 5 , 6 . Intraindividual variability in midazolam and warfarin AUC and C max were assumed to be ~20% 46 48 . Secondary outcomes, t 1/2 and t max , were evaluated using a paired two‐tailed Student's t ‐test on log‐transformed data or Wilcoxon signed‐rank test as appropriate, with 90% confidence intervals and ranges reported for t 1/2 and t max , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Significant differences were noted in the t ½ between the present and previous studies. The t ½ of warfarin was first reported as 36.3 hours, followed with the range of 30 to 60 hours in the continuous studies . After analysis of these literature data, we found that the elimination rate of warfarin would change with different administered dosages, which directly affects the concentration of warfarin.…”
Section: Discussionmentioning
confidence: 90%
“…In the study of Schumaker and Metzler (1998), phenytoin did not appear to be a highly variable drug (the relative standard deviation, RSD, was \20% for C max , and drugs are considered highly variable if RSD C30% (Endrenyi and Midha 1998)) and, since no subject-by-formulation interaction was found, bioequivalence was concluded between the tested formulations both by the average and individual approaches. Although experimentally obtained data on IBE studies do not abound, probably due to the fact that no health authority require IBE studies, other examples of the described situation can be found for other drugs (Yacobi et al 2000;Joukhadar et al 2003;Christians et al 2000).…”
Section: Discussionmentioning
confidence: 99%